Diffuse Solar Micro‐Concentrators Using Dielectric Total Internal Reflection with Tunable Side and Top Profiles. Issue 7 (1st June 2022) - Lin, Yida; Li, Lulin; Ung, Garrett; Lu, Chengchangfeng; Yao, Keyi Kang; Ozbolt, Alex; Guo, Eric; Thon, Susanna M.
Abstract : Solar technology candidates for building‐integrated photovoltaics and mobile power applications suffer from difficulty in fabricating large‐area, defect‐free solar cells, high materials costs, and small angular acceptance for incoming radiation. Solar concentrators collecting non‐normal‐incidence radiation and diffuse light while retaining high concentration ratios are therefore an enticing technology for high‐efficiency‐low‐cost photovoltaic systems. Here, a novel implementation of dielectric total internal reflection concentrators (DTIRCs) utilizing a piecewise smooth sidewall profile with an intermediate segment is developed. Coupled with a turning point in the entrance surface, this design allows for a tunable phase shift between the two sidewall segments, thereby allowing both the concentration ratio at normal incidence and the maximum acceptance angle to be increased, and the limit imposed by etendue conservation to be potentially exceeded under specific conditions. Scalable fabrication techniques are used to produce flexible DTIRCs, and their performance is verified with high‐efficiency commercial solar cells. Moreover, the collectible sun power over the course of a year is calculated, demonstrating that the new design receives more total power compared to traditional direct solar concentrators and standard DTIRC designs in realistic conditions, making it a good candidate for scalable micro‐concentrator systems that can be integrated directly into a solar cell package. Abstract : Solar micro‐concentrators that collect non‐normal‐incidence radiation are a promising technology for high‐efficiency low‐cost photovoltaics. This work demonstrates a new method for theoretically and experimentally tuning the profile of a dielectric total internal reflection concentrator that is able to nominally exceed the limit imposed by etendue conservation under certain conditions, paving the way for mobile and building‐integrated applications.